Sweet-potato callus culture and behaviour in saline medium - Castro, Oneide Ferreira de Andrade; Andrade, Arnóbio Gonçalves de (Pesquisa Agropecuaria Brasileira, 1998)
Aiming at the evaluation of sweet-potato (Ipomoea batatas (L.) Lam.) as to calli production in different phytormone supplements and their response to increase NaCl concentration, petiole explants of nine cultivars were innoculated on the Murasshige & Skoog medium supplemented with 2.21 or 1.0 mg/L of 2,4-D, combined or not with 0.0025 mg/L of BAP. Differences on rate and size of calli according to cultivar or medium were observed. The best results were found on the Arroba cultivar in medium suplemented with 2,4-D (2.21 mg/L) + BAP (0.0025 mg/L). The cultivar Vitoria Roxa did not develop callus. Saline stress reduced calli growth, aiming at ranking cultivars according to its decreasing salinity tolerance, as follows: Arroba, Co-Roxa, RC 1.8, Co-Branca, TR 3, Mãe-de-Família També, Paulistinha and 473.